2017
DOI: 10.15451/ec2017-07-6.7-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobiology and research on Global Environmental Change: what distinctive contribution can we make?

Abstract: Several reports have shown that communities of small farmers are the most vulnerable to global environmental change (GEC). Others have revealed that societies which can count on a rich body of traditional ecological knowledge (TEK) are more resilient in facing this challenge, since their behaviour is already adaptive in character. Within this scenario, the IPCC establishes the need for "cross fertilisation" between TEK and scientific knowledge (SK). But how can we arrive at interpretative agreements when these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
0
20
0
6
Order By: Relevance
“…A nivel mundial, existe un amplio consenso en la necesidad de incorporar el conocimiento ecológico local (CEL) para lograr objetivos de conservación y sostenibilidad de los socio-ecosistemas (Berkes et al 2000;Ladio 2017;Garnett et al 2018). Dada su alta dependencia por los recursos naturales, las comunidades locales e indígenas son más vulnerables que otros sectores sociales frente al actual contexto de cambio global (Ladio y Lozada 2000;IPBES 2019).…”
Section: Introductionunclassified
“…A nivel mundial, existe un amplio consenso en la necesidad de incorporar el conocimiento ecológico local (CEL) para lograr objetivos de conservación y sostenibilidad de los socio-ecosistemas (Berkes et al 2000;Ladio 2017;Garnett et al 2018). Dada su alta dependencia por los recursos naturales, las comunidades locales e indígenas son más vulnerables que otros sectores sociales frente al actual contexto de cambio global (Ladio y Lozada 2000;IPBES 2019).…”
Section: Introductionunclassified
“…Within this scenario it is essential to review government strategies and conservation plans, which are always top-down. The inclusion of bottom-up perspectives on the subject of firewood is necessary in order to find solutions that take local management and cosmologies into account in an inclusive way (Ladio, 2017). Our empirical information reveals that the inhabitants of Patagonia are creating new environments with richness and versatility of use, and seeking new alternatives in the face of firewood scarcity, through landscape domestication.…”
Section: Discussionmentioning
confidence: 99%
“…), flora and populations all coevolve. Thus, complementary use of the landscape, selection of species that grow quickly after harvesting and innovation in supply strategies (purchase), understood as local responses to the problem of change (Ladio, 2017), promote faster recuperation of the landscape and woody species, decreasing uncertainty and increasing biocultural resilience (Ladio, 2017;Morales et al, 2017). For example, some informants revealed that since many people have started buying firewood, regeneration of native plants such as Retanilla patagonica has been observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers from different disciplines have agreed that humans have modified environments throughout history to favor their survival, producing persistent effects (Laland et al 2010;Levis et al 2017;Sullivan et al 2017). In this case, new generations inherit modified environments that result from past decisions, and this may affect the knowledge and current use of plants for different uses (Albuquerque et al 2018;Lins Neto & Albuquerque 2018), especially in the face of climate change (see Ladio 2017).…”
Section: What Theoretical Innovations Can Capture the Dynamic Nature mentioning
confidence: 99%